2002
DOI: 10.1053/rmed.2002.1368
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in the management of asthma and attitudes towards complementary medicine

Abstract: Patients with asthma have many barriers in the way of optimal treatment. These include a failure to recognize warning symptoms, belief in a permanent cure; not continuing treatment for as long as needed; and, an inclination to seek complimentary medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Among adults with asthma, prevalence rates of CAM use range from 6 to 79% in adults (17)(18)(19)(20) and 13-89% in children and adolescents with asthma (21)(22)(23)(24). Adolescents with asthma have been reported to use CAM for a variety of reasons including improved symptom management, concerns about and/or dissatisfaction with conventional therapies, and a belief in "more natural," alternative methods (8,25).…”
Section: Introductionmentioning
confidence: 99%
“…Among adults with asthma, prevalence rates of CAM use range from 6 to 79% in adults (17)(18)(19)(20) and 13-89% in children and adolescents with asthma (21)(22)(23)(24). Adolescents with asthma have been reported to use CAM for a variety of reasons including improved symptom management, concerns about and/or dissatisfaction with conventional therapies, and a belief in "more natural," alternative methods (8,25).…”
Section: Introductionmentioning
confidence: 99%
“…One may be inaccurate symptom assessment or underestimation of asthma severity. In an India-based questionnaire survey of Indians, the majority of patients were unable to assess their symptom severity with only 11.9% able to perceive warning signs of an acute attack [25]. A similar study undertaken in India compared the accuracy of parents and their children in recognising asthma severity symptoms and noted 62% and 60% accuracy respectively [26].…”
Section: Resultsmentioning
confidence: 99%
“…Several randomized controlled trials done with patients with allergies or asthma have shown benefits from yoga postures and breathing. [11][12][13] Nevertheless, it is difficult to establish controls for all subjects following the same practice so that inconsistent effects are oftentimes observed.…”
mentioning
confidence: 99%